Pengaruh Insentif Finansial dan Insentif Non Finansial Terhadap Motivasi Kerja Karyawan pada CV. Sinar Telekom Kabupaten Lahat - Heri Fitriadi; Hardiyansyah (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2020)
This study aims to determine the effect of financial incentives on employee performance CV. Sinar Telekom Lahat regency, the influence of financial and non financial incentives on employee motivation CV. Sinar Telekom Lahat regency, the influence of financial and non financial incentives simultaneously to CV. Telekom rays District. The sample in this study amounted to 47 respondents were distributed to employees CV. Sinar Telekom Lahat regency. Data analysis method used is quantitative analysis using validity, reliability test, normality test, multiple linear regression analysis and test the average difference. The result of financial incentives and significant positive effect on work motivation. It can be seen from the value t count > t table (4.793 > 2.015) and values. Nonfinancial incentives and significant positive effect on employee motivation. It can be seen from the value t count > t table (2.356 > 2.015). Incentives and financial and non-financial incentives simultaneously positive and significant impact on employee motivation. It can be seen from the value of F count> F table (44.227 > 3.23) and the significance value <significance level (α) 0.05 (0.000 < 0.05).